Understanding the Essence of Islamic Education: Investigating Meaning, Essence, and Knowledge Sources - M Mahmudulhassan; W Waston; M Muthoifin; Saif Uddin Ahmed Khondoker (Walidem Institute and Publishing (WIP), 2024)
Islamic tradition pays great importance to education, considering it as both a means of obtaining knowledge and a route to moral and spiritual enlightenment. This article attempts to close the gap in the literature by conducting an extensive analysis of the foundations of Islamic education. The different aspects of Islamic education, including its pedagogical principles, philosophical foundations, and contemporary relevance, are investigated in this study using an interdisciplinary qualitative method that combines sociology, philosophy of education, and Islamic studies. To make clear the basic objective of Islamic education that is, to develop individuals intellectually, morally, socially, and spiritually via Islamic teachings the research examines the purposes of Islamic education and the knowledge-gathering method it offers. This investigation highlights the ability of Islamic education to promote ethical leadership in the contemporary world and the transforming role that it plays in moulding people and civilizations.